KEMAMPUAN TENURE AUDIT SEBAGAI PEMODERASI PENGARUH UKURAN PERUSAHAAN PADA AUDIT REPORT LAG - Yuni, Ida Ayu Eka Purnama; Dwirandra, AANB (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
This study aims to determine the audit tenure as the moderating influence of firm size on audit report lag. The population in this research is manufacturing companies listed in Indonesia Stock Exchange 2009-2014 period. The samples used as many as 34 companies by purposive sampling method. The analysis technique used is Moderated Regression Analysis (MRA). Based on the analysis and hypothesis testing, then we got the conclusion that (1) the size of the company's negative effect on the audit report lag which shows that the bigger the company, the shorter the audit report lag, (2) tenure audit able to moderate (strengthen) the effect of firm size on audit report lag which shows that companies are audited by an auditor to audit the long tenure has a level of audit report lag is low. Completion of the audit will be faster if the auditors audit the audit firm with long tenure at a large company.
Keywords: Audit Report Lag, Company Size, Tenure Audit